Declarative memory impairments in post-traumatic stress disorder and cardiovascular reactivity - Erla Katrín Jónsdóttir 1992- (2021)
Post-traumatic stress disorder (PTSD) has been associated with cognitive deficits, with the most prominent effects on declarative memory, including short- and long-term semantic and episodic memory. Additionally, PTSD has been associated with both amplified and diminished cardiovascular reactivity, which in turn has been associated with inferior cognitive performance. The present study examined the effects of PTSD on memory and cardiovascular reactivity in response to cognitive tasks. In addition, the relationship between cardiovascular reactivity and memory was explored. Students at Reykjavík University completed the PTSD checklist for DSM-V (PCL-5) (n=44). Of those, 13 met the criteria for PTSD, and 31 did not. Participants completed the Logical Memory Scale, and cardiovascular reactivity was measured simultaneously. Valid cardiovascular measures were obtained from 31 participants. Individuals with PTSD displayed significant deficits specific to episodic memory and non-significantly diminished blood pressure (BP) responsivity compared to individuals without PTSD. BP reactivity correlated significantly with episodic memory performance. These results suggest that declarative memory deficits in PTSD are specific to episodic memory. Diminished BP responses in PTSD might account for episodic memory deficits. More research is needed with larger sample sizes to clarify the relationship between PTSD, cardiovascular reactivity, and memory. Keywords: Post-traumatic stress disorder (PTSD), cardiovascular reactivity, declarative memory, semantic Memory, episodic Memory Áfallastreituröskun hefur verið tengd við skerta hugræna getu, sérstaklega hvað varðar meðvitað minni, bæði skammtíma og langtíma þekkingar- og atburðarminni. Áfallastreituröskun hefur einnig verið tengd bæði aukinni og minnkaðri svörun í hjarta- og æðakerfi. Afbrigðileg svörun í hjarta- og æðakerfi hefur verið tengd verri hugrænni getu. Í þessari rannsókn voru áhrif áfallastreituröskunnar á meðvitað minni skoðuð og svörun í hjarta- og æðakerfi við ...